PEMBERDAYAAN KELOMPOK TANI DALAM PENYEDIAAN PUPUK PADA USAHATANI PADI SAWAH (Oryza sativa L.) - Effendy, Lukman; Surohman, Surohman (Jurnal Penyuluhan Pertanian, 2012)
This study is to carry out from March up to May 2010. This study is aimed to explain how does empowerment of farmer group enableness in supplying fertilizer for rice business plants at district Tembilahan Regency Indragiri. Study result shows that group enable passes group function as class learns; has value rangking bottommost/atonic, cooperation vehicle; togetherness effort with side has bottommost/atonic value, and production unit; exertion rdk and RDKK has bottommost/atonic value. While level empowerment or group ability in supplying fertilizer correctly; fertilizer availability in area occupies value rangking bottommost, and ability in look for alternative other in fertilizing; extension agent character in get and submit has value rangking bottommost/atonic. weaknesses necessary be repaired to pass institute organization character at village level so that farmer group institute function can increase enableness level in supplying fertilizer to rice business.